f(x) = ax^7 + bx^3 + cx -7

f(7) = a(7)^7 + b(7)^3 + c(7) -7 = 7

==> (7^7)a + (7^3)b + 7c = 14.........(1)

f(-7) = a(-7)^7 + b (-7)^3 + c(-7)-7

= -1(a(7^7) - b (7^3) - c(7) - 7

= -[ a(7^7) + b(7^3) +...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

f(x) = ax^7 + bx^3 + cx -7

f(7) = a(7)^7 + b(7)^3 + c(7) -7 = 7

==> (7^7)a + (7^3)b + 7c = 14.........(1)

f(-7) = a(-7)^7 + b (-7)^3 + c(-7)-7

= -1(a(7^7) - b (7^3) - c(7) - 7

= -[ a(7^7) + b(7^3) + 7c)] -7

But from (1) we know that inside brackets equals 14

= => -(14) -7 = -21

==> **f(-7) = -21**